THE PRACTICE OF EIGHT FAMILY FUNCTIONS: DIFFERENCES BETWEEN RURAL AND URBAN AGING FAMILIES IN INDONESIA - Pujihasvuty, Resti; Nasution, Sri Lilestina; Naibaho, Margareth Maya P; Fajarningtiyas, Desy Nuri (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The family is essential in improving the older adults’ quality of life, where the family's role can be reflected in the eight family function practices: 1) Religious; 2) Sociocultural; 3) Love; 4) Protection; 5) Reproductive; 6) Socio-education; 7) Economic; and 8) Environmental. This study aimed to determine the differences in family function practices among aging families in rural and urban areas. Data were analyzed using Cross-Tabulation with the Chi-Square and Independent T-test from a sample of 12,391 aging families in the 2019 Program Accountability Performance Survey. The results of the Independent T-test p<0.001 indicate a significant difference in implementing each family function between aging families in urban and rural areas. Despite both regions' low index scores for eight family function practices, aging families in the urban area practice slightly better than aging families in the rural. The characteristics that distinguished the implementation of family functions in urban and rural areas were educational and economic factors. In aging families, economic and love functions are most commonly performed in rural and urban areas, whereas reproductive and educational functions are the least performed. This research suggests intensively socializing about the eight family functions and educating on the importance of reproductive and educational functions in improving the quality of life in aging families.